1995
DOI: 10.1002/jor.1100130513
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between synthetic activity and glycosaminoglycan concentration in epiphyseal cartilage raises questions about the regulatory role of interstitial pH

Abstract: Current data provide compelling evidence that the pH of the interstitial fluid of cartilage is an important determinant of the metabolic activity of chondrocytes, and this has served as the basis for a mechanistic proposal whereby chondrocytes could sense mechanical compression. The objective of the current study was to test this hypothesis further by examining biosynthetic activity in cartilage as a function of glycosaminoglycan content, which is the major determinant of interstitial pH. On the basis of previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The specific mechanisms by which chondrocytes detect mechanical signals and convert them to an intracellular biochemical response are not fully understood. However, depending on the mechanical condition applied (e.g., shear forces, tensile stress, compression, hydrostatic pressure), several signal transduction pathways have previously been found to be involved, including integrin-mediated pathways, stretchactivated or -inactivated ion channels, the cytoskeleton, decreased pH, electrical streaming potentials, nitric oxide, or activating second messenger systems (Boustany et al 1995;Das et al 1997;Millward-Sadler et al 2000;Wright et al 1996). Thus, the mechanical signal perceived by the chondrocytes influences the pathways subsequently used by the cells, resulting in different metabolic activities.…”
Section: Discussionmentioning
confidence: 99%
“…The specific mechanisms by which chondrocytes detect mechanical signals and convert them to an intracellular biochemical response are not fully understood. However, depending on the mechanical condition applied (e.g., shear forces, tensile stress, compression, hydrostatic pressure), several signal transduction pathways have previously been found to be involved, including integrin-mediated pathways, stretchactivated or -inactivated ion channels, the cytoskeleton, decreased pH, electrical streaming potentials, nitric oxide, or activating second messenger systems (Boustany et al 1995;Das et al 1997;Millward-Sadler et al 2000;Wright et al 1996). Thus, the mechanical signal perceived by the chondrocytes influences the pathways subsequently used by the cells, resulting in different metabolic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Acidification of the extracellular pH has been shown to modify protein and proteoglycan synthesis in intervertebral disc explants (9) and to inhibit matrix synthesis in human chondrocytes (10) and calf epiphyseal cartilage (5). A bimodal response to extracellular pH has been noted on matrix synthesis for bovine chondrocytes (11, 12), calf epiphyseal cartilage (13), and intervertebral disc slices (9), where matrix synthesis is greatest at normal cartilage pH (pH 7.0−7.2) (12) or at extracellular pH values close to that found for the disc in vitro (about pH 6.9−7.2) (9), and alkalinization or acidification will decrease matrix synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these physical phenomena may potentially act as a "mechano-ligand" activating or inhibiting one or more signaling pathways. Prior studies have often focused on the effects of one or a few of these components of compressive loading such as negative fixed charge density (26) or interstitial pH (22,29,30). Recent studies have also demonstrated that mechanical stretching of chondrocytes can increase nitric oxide production (31) and alter membrane transport phenomena, resulting in proliferative changes (32).…”
mentioning
confidence: 99%